Investigation of the difference between the low frequency limit of the impedance spectrum and the slope of the polarization curve. (20th October 2015) - Chandesris, M.; Robin, C.; Gerard, M.; Bultel, Y.
Abstract: Analysis of both polarization curve and Electrochemical Impedance Spectroscopy (EIS) provides meaningful information about the electrochemical behavior of Proton Exchange Membrane Fuel Cells (PEMFC). Nevertheless, the interpretation of the electrochemical responses remains complex without the use of physics-based models. This paper investigates the experimentally observed and unexpected difference between the low frequency resistance of a cell and the slope of the polarization curve. A 0D stirred tank model is proposed to analyze the experimental data and a simple relation is obtained linking the two resistances difference with the air stoichiometry. Furthermore, it is shown that, until moderate current densities, the low frequency loop of the impedance spectra can be associated to oxygen transport limitation due to convective oxygen supply along the channel, without having to resort to diffusion limitations. Finally, the equivalent electrical circuit (EEC) corresponding to this model is built as a tool to process results from other tests.